Epidemiological Evaluation of Suicidal Deaths due to Hanging: A Retrospective Medicolegal Study in Sylhet (IAHS Medical Journal, 2024)
Background: Suicidal hanging is the most common method of suicide in developing countries, especially among young people. During conventional autopsies, it is one of the significant causes of unnatural deaths in Bangladesh. This study was performed to determine the epidemiological evaluation of suicidal deaths due to suicidal hanging at the mortuary of the Forensic Medicine Department of Sylhet MAG Osmani Medical College, Sylhet.Materials and methods: An autopsy record-based retrospective study carried out to ascertain the epidemiological evaluation of 340 cases of suicidal hanging deaths from January 2015 to December 2018 in the Department of Forensic Medicine, Sylhet MAG Osmani Medical College, Sylhet.Results: Hanging was more common in the age ranges of 10-19 years (33.0%) and 20-29 years (29.1%), accounting for nearly two-thirds (62.1%) of all deaths. The incidence was higher in females (59.3%) than males (46.7%). Gowainghat (12.1%) and Kotwali (9.5%) had the highest incidences of victims. The most common autopsy findings were that the subcutaneous tissues underneath the ligature mark were found to be pale, white, hard and glistening in 94.2% of cases, cyanosis was found in 89.8% of cases, dribbling of saliva was seen in 66.3% of cases and subconjunctival petechial haemorrhage was observed in 46.0% of cases. Asphyxia (93.3%) was the most common cause of suicidal hanging deaths identified during autopsy.Conclusion: The majority of victims were female and young individuals were especially vulnerable to suicidal ideation, attempts and suicide by hanging. To reduce suicides, awareness programs, psychological counseling andsuicidal behavioral treatment are recommended.IAHS Medical Journal Vol 7(1), June 2024; 13-16